2023
DOI: 10.1002/ccr3.6854
|View full text |Cite
|
Sign up to set email alerts
|

Distalization using efficient attachment protocol in clear aligner therapy—A case report

Abstract: To describe an esthetic orthodontic treatment using aligners in an adult patient with dental class II malocclusion associated with crowding. A 25-year-old female patient with skeletal class I, bilateral class II relation, increased overjet and overbite and crowding in both arches presented for orthodontic treatment. The patient refused conventional fixed multibracket treatment in favor of aligners. Pre-and post-treatment records are presented. Treatment objectives were achieved in 10 months, and the patient wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…It has been reported in the literature that the clinical discrimination threshold of CIE76 color difference is 1.0-3.7 for restorations or intraoral teeth (Johnston and Kao, 1989;Seghi et al, 1989;Pandian et al, 2017). In this study, (Sabouni et al, 2023),we found that within the first 10 days of bleaching treatment, the color change (ΔE) of isolated teeth changed by more than 4 chromatic aberration units; this was higher than the discernibility threshold reported in the literature, thus indicating that the color change of isolated teeth was discernible by eye. Subsequently, the rate of tooth color changed more slowly, reaching 8.65 color difference units at 40 days.…”
Section: Discussionmentioning
confidence: 66%
“…It has been reported in the literature that the clinical discrimination threshold of CIE76 color difference is 1.0-3.7 for restorations or intraoral teeth (Johnston and Kao, 1989;Seghi et al, 1989;Pandian et al, 2017). In this study, (Sabouni et al, 2023),we found that within the first 10 days of bleaching treatment, the color change (ΔE) of isolated teeth changed by more than 4 chromatic aberration units; this was higher than the discernibility threshold reported in the literature, thus indicating that the color change of isolated teeth was discernible by eye. Subsequently, the rate of tooth color changed more slowly, reaching 8.65 color difference units at 40 days.…”
Section: Discussionmentioning
confidence: 66%
“…This case was considered among the most challenging to treat according to available literature. However, the study concluded that appropriate attachment selection was an effective means of treating such cases [52]. The expertise demonstrated in this study, particularly in the judicious selection and application of attachments, is highly appreciated and serves as a testament to the skillful and innovative approaches required in advanced orthodontic treatments like CAT.…”
Section: Orthodontist's Role and Decision-makingmentioning
confidence: 81%
“…Sabouni et al showcased a complex case involving a 25-year-old female patient with a class I skeletal relationship, bilateral class II dental relationship, increased overjet, deep bite, and crowded maxillary and mandibular arches [52]. This case was considered among the most challenging to treat according to available literature.…”
Section: Orthodontist's Role and Decision-makingmentioning
confidence: 99%
“…The results indicated that distalization of the first molars can be achieved without significant inclination or vertical movement [70]. According to a study carried out by Sabouni et al, in 2023, the combined use of aligners with appropriate position and attachment geometry is an effective means of solving more complex orthodontic problems such as Class II malocclusions in a comparable time frame, if not inferior to conventional fixed orthodontics but with excellent aesthetics, oral hygiene and quality of life [66,85]. CAT, in a study model by Jia et al, with 3D anchor attachments, could be effective in controlling the rotation and tipping of the anchor units caused by the 3D anchor attachment, which confirmed that the CA could improve root movement [67,86].…”
Section: Discussionmentioning
confidence: 99%